GAMBARAN KADAR KALSIUM DARAH PADA WANITA MENOPAUSE DI DESA SINABUN, KECAMATAN SAWAN, KABUPATEN BULELENG - Cok Dewi Widhya (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
ABSTRACTBackground: Menopause women will get a decrease in estrogen hormones that cause decreases of blood calcium level. If the calcium level in the blood is low then the body will take calcium from the bone to perform body functions, this causes calcium levels in the bones decreased so it caused osteoporosis.Methode: This study is a descriptive study which describes blood calcium levels in menopause women in Sinabun Village, Sawan District, Buleleng Regency. The study was conducted from February until June 2017 with a population of 186 people and sample of 30 people selected by systematic random sampling technique. Measurement of blood calcium level using NM-BAPTA method.Result: The results showed that 17% of respondents had low blood calcium levels and 83% of respondents had normal blood calcium levels with an average blood calcium level is 9.20 mg/dL.Conclusion: The decrease of blood calcium levels occurred in respondents of age ≥60 years old, the respondents with the old menopause period 10 years, the respondents who work as housewife and traders, the respondents who never consumed high calcium milk, and the respondents who didn’t have history of hypoparathyroidism and kidney disorders.Keyword: blood calcium, menopause.